KINERJA PEGAWAI DINAS PERTANAHAN DAN TATA RUANG KOTA YOGYAKARTA DI MASA PANDEMI COVID-19 MELALUI WFH (WORK FROM HOME) - Albashori, Muhammad Fatkhurohman; Mursyid, Mursyid; Wijayanti, Irine Diana Sari (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
The purpose of this study was to find out 1) the per formance of employees during the Covid-19 pandemic at the Yogyakarta Land and Spatial Planning Office, 2) the obstacles in implementing WFH (Work From Home) during the Covid-19 pandemic at the Yogyakarta Land and Spatial Planning Service and 3) the efforts made by the Yogyakarta Land and Spatial Planning Office to analyze the constraints of WFH (Work From Home). The results of the study obtained information that 1) Employee performance in WFH (Work From Home) during the Covid-19 pandemic was good, the quality of work remained the same as before the Covid-19 pandemic with the responsibility, initiative and discipline of employees, because the output targets must still be met same. 2) Constraints experienced include network and time, but do not reduce the quality of employees because any problems that occur will be directly coordinated together in the work group. 3) Efforts are being made to implement SPIP (Government Internal Control System).